The Effect of Marketing Mix on Purchase Intention in the Home Appliance Industry in West Java - Dyah Puspita Sari; Prawira Fajarindra Belgiawan (UNIVED Press, 2024)
The purpose of this research is to discover what factors influence someone's decision to purchase home equipment. In this study, a discussion was held about the effect of the 4P marketing mix elements on purchase intention. The product, the price, the place, and the promotion are the four marketing aspects that will be discussed in this paper. The respondents in this study were 234 people who met the requirements of being of productive age, living in West Java, and having a fixed income. SEM-PLS was used to analyze the data, and the results revealed that just three variables from the marketing mix affected customer purchase intention in the home appliances industry. Product, price, and promotion are the variables that influence purchase intention; however, place has no effect. The company can pay attention to these three variables while designing strategies to improve market competition.